PENGARUH SUKU BUNGA SBI, NILAI TUKAR, DAN INDEKS PASAR DUNIA PADA IHSG DI BEI - Nugraha I Wayan Wahyu; Dewi Made Rusmala (Faculty of Economics and Business Udayana University, 2015)
Composite Stock Price Index (CSPI) is an indicator that used to know the progress of the Indonesian capital market, so can be used as a reflection of Indonesian National Economy . CSPI is influencedby several factors, including interest rates, exchange rates, in particular US market index (Dow Jones) and market index of Japan (Nikkei 225). The purpose of this study is to determine the effect ofSertifikat Bank Indonesia (SBI) interest rate, exchange rate, the Dow Jones and the Nikkei 225 Indexes on CSPI. This study used 60 samples, which consists of monthly data of all variables during the year 2009-2013. The data were analyzed by using multiple linear regression. The findings show that SBI interest rate and exchange rate has a negative effect on CSPI. Meanwhile, the Dow Jones and the Nikkei 225 Indexes has a positive impact on CSPI.